2017
DOI: 10.1016/j.celrep.2017.06.066
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feedback Loop between Sestrin2 and mTORC2 Is Required for the Survival of Glutamine-Depleted Lung Cancer Cells

Abstract: Proper regulation of mTORC1 and mTORC2 upon nutrient starvation is critical for cancer cell survival. Upregulation of Sestrin2 in response to glutamine deprivation rescues cell death by suppressing mTORC1. However, the contribution of mTORC2 to Sestrin2-mediated mTORC1 suppression remains unclear. Here, we report that both Sestrin2 and mTORC2 are upregulated in glutamine-depleted lung cancer cells. Moreover, glutamine depletion caused Sestrin2 to associate with mTORC2, which was required for the increase in Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 32 publications
2
62
0
Order By: Relevance
“…The decrease in intracellular levels of both glutamine and glutamate under SESN2down-regulated conditions and their increase post-SESN2 overexpression indicated that Sestrin2 did have a link to the glutamine levels in cells, but certainly it did not regulate the conversion of glutamine to glutamate because there was no accumulation of glutamine, which would have normally occurred if the conversion of glutamine to glutamate was blocked. A recent study has shown that SESN2 promotes survival of cancer cells by inhibiting mTORC1 and activating mTORC2 signaling under depletion of glutamine [20]. Our studies showing silencing of SESN2 expression under glucose limitation (adequate glutamine) negatively regulating mTORC2 while activating mTORC1 suggests that under differential metabolic stressors, SESN2 may act as a sensor that promotes cancer cell survival by positively regulating mTORC2, which in turn regulates mTORC1.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The decrease in intracellular levels of both glutamine and glutamate under SESN2down-regulated conditions and their increase post-SESN2 overexpression indicated that Sestrin2 did have a link to the glutamine levels in cells, but certainly it did not regulate the conversion of glutamine to glutamate because there was no accumulation of glutamine, which would have normally occurred if the conversion of glutamine to glutamate was blocked. A recent study has shown that SESN2 promotes survival of cancer cells by inhibiting mTORC1 and activating mTORC2 signaling under depletion of glutamine [20]. Our studies showing silencing of SESN2 expression under glucose limitation (adequate glutamine) negatively regulating mTORC2 while activating mTORC1 suggests that under differential metabolic stressors, SESN2 may act as a sensor that promotes cancer cell survival by positively regulating mTORC2, which in turn regulates mTORC1.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, the same study also suggests SESN2 as a possible methionine sensor under leucine starvation, which may further influence mTOR activation . Apart from acting as a leucine sensor, SESN2 has been recently reported to induce a positive feedback loop with mTORC2 for survival of glutamine‐deprived cancer cells . We enquired if SESN2 can induce metabolic reprogramming under glucose starvation (provided glutamine is abundant) in cancer cells and if so how that impacts PGC‐1α levels.…”
Section: Introductionmentioning
confidence: 89%
“…It is interesting to note that glutamine depletion decreases mTORC1 activity while increasing mTORC2 activity [54,141]. This differential regulation of mTORC1 and mTORC2 is mediated by sestrin2 and allows survival of these cancer cells by maintenance of energy and redox balance [141]. However, inhibition of glutaminase or GDH did not affect Akt phosphorylation while it diminished mTORC1 activation [29].…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…mTORC2 also responds to levels of glutamine or its catabolites. It is interesting to note that glutamine depletion decreases mTORC1 activity while increasing mTORC2 activity [54,141]. This differential regulation of mTORC1 and mTORC2 is mediated by sestrin2 and Glutamine is a versatile molecule, as it serves as an alternative carbon source for energy production and its carbon and nitrogen are also used for biosynthetic reactions [130].…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…Mitochondrial proficiency and ROS detoxification are critical for cancer cell viability 26 , and proliferating cancer cells must preserve intracellular ATP and NADPH levels through mitochondrial oxidative phosphorylation and the prevention of excessive ROS accumulation 27 . In silico analyses of the DEGs also suggested that the results were in line with mitochondrial dysfunction during the first period.…”
Section: Discussionmentioning
confidence: 99%